Laparoscopic Davydov Procedure for Creation of Neovagina in MRKH Syndrome - Ratih Krisna; Rizky Agustria (HM Publisher, 2021)
Introduction: The Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is a condition in which there is an absence of the uterus and the upper part (2/3) of the vagina. Women with MRKH syndrome show normal development of secondary sexual characteristics and a normal 46, XX karyotype. MRKH syndrome is a common cause of primary amenorrhea. Ultrasonography examination confirms kidneys, presence of the ovaries, and absence of uterus. Treatment should include a multidisciplinary approach to create a functional vagina. One of the procedures is laparoscopic Davydov vaginoplasty. Aim: To report MRKH syndrome case treated with laparoscopic Davydov vaginoplasty. Method: Ms. A, 21 years old, P0A0, came to FER clinic Moh. Hoesin Hospital Palembang with complaint, never had menstruation, the patient admitted her breast, and her pubic had growth. She wants to get married in the next six months. From the US result, there was non visualized uterus, genital band (+), and both ovaries within normal limit MRKH Syndrome. Karyotype Examination: 46, XX. Patient was diagnosed with primary amenorrhea caused by MRKH syndrome and was planned for neovagina (Davydov Procedure). Result: A woman 21-year-old, P0A0, was diagnosed with primary amenorrhea caused by MRKH syndrome. The Davydov procedure was done to create a neovagina. Intraoperative, after protrusion of the wood mold as a marker shown, an incision is made to the left and right side so that the mold penetrates the abdominal cavity, then the mold is pulled into the vaginal canal slowly. The anterior and posterior peritoneal layers are drawn into the vaginal canal. The anterior and posterior peritoneal layers were withdrawn with an ovum clamp and then interrupted suture. The anterior and posterior peritoneal layers were sutured in a circular method to form a vaginal cuff. The vaginal wall is sutured (interrupted) to hold mold fixed. Conclusion: MRKH syndrome is a disorder that occurs in females and mainly affects the reproductive system. This condition causes the vagina and the uterus to be underdeveloped or even absent at birth. Patients with diagnosed MRKH syndrome require interdisciplinary care. Davydov procedure is a laparoscopically-assisted technique, which has an advantage over traditional approaches. It has shorter operating time, lower intraoperative complications, shorter hospital stay, and no external scars. Postoperatively, sexual function is similar to women without gynecological disorders.